Carbon saving potential of urban parks due to heat mitigation in Yangtze River Economic Belt. (20th January 2023) - Chen, Mo; Jia, Wenxiao; Du, Chunlei; Shi, Manqing; Henebry, Geoffrey M.; Wang, Kai
Abstract: Urban parks are considered as an effective, sustainable, and affordable heat mitigation strategy. At present, there is a lack of understanding of the carbon saving potential of urban parks in the context of urban warming. Here we provide a simple approach to estimate the potential carbon savings due to heat mitigation based on analysis of 1510 parks in 26 major urban areas of the years 2017–2021 within the Yangtze River Economic Belt (YREB), China's largest sustainability experiment. On average, an urban park with 26.9 ± 1.5 ha in the YREB could avoid 23.7 ± 1.6 t CO2 (1.08 ± 0.03 t CO2 /ha) in emissions due to heat mitigation per summer day. Considered altogether, the 1510 urban parks can offset 5.37% of the daily fossil fuel emissions in the YREB. To boost carbon saving efficiency, lush vegetation should be first considered and the coupled green and blue infrastructures are always advocated. The total parks carbon saving of cities gradually improved along the Yangtze River from west to east, among which Shanghai city (in the east of the YREB) is with the largest amount (4341 t CO2 ). The strategies using exquisite landscape design for improving carbon saving may differ across different climate zones. These findings can inform decision-making for urban sustainable development and climate change mitigation, which may benefit China's movement toward carbon neutrality.